INDENTIFIKASI FAMILI ZINGIBERACEAE DI KAWASAN HUTAN GUNUNG BUA KERINCI - Tomi Apra Santosa; Sisi Yulianti (Universitas Pakuan, 2020)
Zingiberaceae is a family of ginger plants found in the forest area of Mount Bua Kerinci. However, many species of the family have not been properly identified. This research aims to find out the type of family Zingiberaceae in the forest of Mount Bua Hill. This type of research is qualitative research with exploratory survey methods. The data collection techniques used are observation and documentation. The results showed that the family species zingiberaceae found are 5 clans and 9 Species namely Curcuma domestica (Turmeric), Zingiber aromaticum (Lempuyang), Etlingera elatior (Kecombrang), Curcuma Heyneana (Temu Giring), Curcuma aeruginosa (Black Meeting), Curcuma zedoria (White Meet), Zingiber cassumunar (Bangle), Amomun maximum (Cardamom), Kaemperia galanga (Kencur).